2014
DOI: 10.1021/es404598v
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Industrial PVP-Stabilized Silver Nanoparticles in Saturated Quartz Sand Coated with Pseudomonas aeruginosa PAO1 Biofilm of Variable Age

Abstract: Understanding the environmental fate and transport of engineered nanoparticles (ENPs) is of paramount importance for the formation and validation of regulatory guidelines regarding these new and increasingly prevalent materials. The present study assessed the transport of an industrial formulation of poly(vinylpyrrolidone)-stabilized silver nanoparticle (PVP-nAg) in columns packed with water-saturated quartz sand and the same sand coated with Pseudomonas aeruginosa PAO1 biofilm of variable age (i.e., growth pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 60 publications
3
50
0
Order By: Relevance
“…Obviously, this research is aimed at clarifying the fundamental mechanism among complex interactions of ENPs transport and deposition in biofilm-laden granular media. However, heterogeneous biofilm, multilayer coating formed from different bacterial species [22], various growth phase [24] or environmental conditions [14,19,25], complicates the interpretation of ENPs transport behavior. Further studies are needed to accurately distinguish the contributions of biofilm on the transport of GONPs and other ENPs in more complex granular media such as natural soils and aquifer sediments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Obviously, this research is aimed at clarifying the fundamental mechanism among complex interactions of ENPs transport and deposition in biofilm-laden granular media. However, heterogeneous biofilm, multilayer coating formed from different bacterial species [22], various growth phase [24] or environmental conditions [14,19,25], complicates the interpretation of ENPs transport behavior. Further studies are needed to accurately distinguish the contributions of biofilm on the transport of GONPs and other ENPs in more complex granular media such as natural soils and aquifer sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al [15] concluded that the greater deposition of ZnO nanoparticles may also contribute to the rougher sand surface with biofilm when comparing SEM images to the bare one. Recently, Mitzel and Tufenkji [24] illustrated biofilm grown on collector surface may be more accurately consisting of patchy or inhomogeneous biofilm coatings. Likewise, Fig.…”
Section: Ments (3 H) As Shown Inmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of recent studies have examined the transport of unmodified and surface-modified AgNPs in saturated porous media (e.g., unmodified AgNPs (Lin et al 2011), citrate-stabilized AgNPs (El Badawy 2011Sagee et al 2012;Taghavy et al 2013), polyvinylpyrrolidone (PVP)-AgNPs Flory et al 2013;Lin et al 2012b;Mitzel and Tufenkji 2014;Sagee et al 2012;Song et al 2011), Gum Arabic-AgNPs (Lin et al 2012a;Song et al 2011), branched polyethyleneimine-coated AgNPs (El Badawy 2011), and proteinate-AgNPs (Ren and Smith 2013). These studies have reported the effect of flow velocity, pH, and ionic strength on AgNP transport.…”
Section: Introductionmentioning
confidence: 99%